2008
DOI: 10.1097/hcm.0b013e31818c810b
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Workplace Violence

Abstract: Violence in the health care workplace is occurring in a covert fashion; it is occurring at the patient bedside. However, data on workplace violence tend to be underreported and relatively scarce. This article identifies and examines the phenomenon of unreported and underreported workplace violence against nursing staff that is virtually hidden. Health care executives need to be attuned to this type of violence because it may significantly affect their ability to recruit and retain nursing staff. This article p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 7 publications
0
2
1
Order By: Relevance
“…Our study also found that male staff had the highest risk of exposure to PV, which is consistent with findings in other countries. Contrary to expectations [ 12 ], male staff were particularly vulnerable to NPV in the specialist hospital. Rotating shift workers had an over three-fold greater odds of PV compared to fixed day shift workers in the Chinese medicine hospitals, and an over two-fold greater odds of PV and an over 1.5-fold odds of experiencing NPV compared to fixed day shift workers in general hospitals.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Our study also found that male staff had the highest risk of exposure to PV, which is consistent with findings in other countries. Contrary to expectations [ 12 ], male staff were particularly vulnerable to NPV in the specialist hospital. Rotating shift workers had an over three-fold greater odds of PV compared to fixed day shift workers in the Chinese medicine hospitals, and an over two-fold greater odds of PV and an over 1.5-fold odds of experiencing NPV compared to fixed day shift workers in general hospitals.…”
Section: Discussioncontrasting
confidence: 70%
“…Their violence caused numerous ill patients to become stressed by the attackers’ presence and several monitors to lose function. Without these monitors—connected to crucial life-sustaining technology—many ICU patients’ lives were put in danger [ 12 ]. As such, violence in medical establishments may lead to the deaths of patients not involved in the dispute.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that aggression is significantly underreported; therefore, the actual prevalence rates may not exactly be representative (Danesh et al 2008;Lanza, 2016). Possible reasons for the under-reporting are the work overload (with failure of documentation), a less supportive work environment and the staff attitude expecting assaults as a part of the job, and considering the incident as minor and isolated or as a normal or functional behavior (Gerberich et al, 2004, Jansen et al, 2006Lanza, 2016).…”
Section: Discussionmentioning
confidence: 99%